PENGGUNAAN MODUL PEMBELAJARAN IPA DENGAN PENDEKATAN INKUIRIDALAM PELATIHAN BERBASIS KOMPETENSI BAGI GURU IPA DI SEKOLAH DASAR - Didin Wahidin (UJMES (Uninus Journal of Mathematics Education and Science), 2016)
Various innovations in the field of education have been carried out to produce the best learning programs that have thepotential to develop students' abilities in mastering teaching material, skills and attitudes of students. But any renewal inan effort to improve the quality of education will lead to learning in the classroom where the main determinant of quality isthe teacher. Therefore, the preparation of qualified teachers will determine the overall quality of education. Forms of qualityteacher preparation are done through competency-based teacher training. To further improve the results in this papersupplemented by the use of inquiry-based modules. The main characteristic of this module is that the inculcation of conceptsis integrated with the inculcation of the underlying reasoning accompanied by the inculcation of science process skills.